Problem-Solving Learning used by Realia Media to Enhance Students' Understanding of Mathematical Concepts Class V SDN 6 Blangpidie - Hayati, Zikra; Aini, Qurrata’; Jarmita, Nida; Herawati, Herawati (azkiya, 2024)
The purpose of this study was to determine the increase in teacher activity, student activity, and student conceptual understanding through the application of problem solving learning models and realia media in class V of SDN 6 Blangpidie. The research method used was Classroom Action Research with 28 fifth grade students. Data collection were used observation and test. Based on the results of the analysis of teacher activity sheet data in cycle I, namely 78.57 (good), in cycle II it increased to 89.28% (very good) and continued to enhance in cycle III to 95.23% (very good). The results of the analysis of student activity sheet data in cycle I were 76.19% (good) in cycle II it increased to 84.52% (very good), and continued to increase in cycle III to 94.04% (very good). The results of the students' conceptual understanding test in cycle I were 72.91% (good), then increased in cycle II to 81.99% (good) and continued to increase in cycle III to 89.72% (very good) and had determined classical completeness. In concluded, the application of the Problem Solving Model and Realia Media can increase effectiveness students' mathematical concept understanding.